2015
DOI: 10.1007/s10802-015-0113-9
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Elementary School Social Experience and Executive Functions Development: Introduction to a Special Section

Abstract: Children's executive functions, encompassing inhibitory control, working memory and attention are vital for their self-regulation. With the transition to formal schooling, children need to learn to manage their emotions and behavior in a new and complex social environment that with age increases in the intensity of social interactions with peers and teachers. Stronger executive functions skills facilitate children's social development. In addition, new experiences in the social environments of school also may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 45 publications
5
40
0
2
Order By: Relevance
“…Arguably one of the best ways to incorporate accuracy and speed of performance into a single set of indices is through a computational approach known as diffusion modelling (Ratcliff & McKoon, 2008). This approach, which has long been used in the cognitive sciences and cognitive neurosciences, has recently begun to be adopted in the developmental (Cohen-Gilbert et al, 2014; Ratcliff, Love, Thompson, & Opfer, 2012), aging (Ratcliff, Thapar, & McKoon, 2004, 2011; Starns & Ratcliff, 2010), and clinical (Huang-Pollock et al, 2016; Huang-Pollock, Karalunas, Tam, & Moore, 2012; Karalunas, Huang-Pollock, & Nigg, 2012; Moustafa et al, 2015; Weigard, Huang-Pollock, & Brown, 2016; Weigard & Huang-Pollock, 2014; Wiecki, Poland, & Frank, 2015) literatures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arguably one of the best ways to incorporate accuracy and speed of performance into a single set of indices is through a computational approach known as diffusion modelling (Ratcliff & McKoon, 2008). This approach, which has long been used in the cognitive sciences and cognitive neurosciences, has recently begun to be adopted in the developmental (Cohen-Gilbert et al, 2014; Ratcliff, Love, Thompson, & Opfer, 2012), aging (Ratcliff, Thapar, & McKoon, 2004, 2011; Starns & Ratcliff, 2010), and clinical (Huang-Pollock et al, 2016; Huang-Pollock, Karalunas, Tam, & Moore, 2012; Karalunas, Huang-Pollock, & Nigg, 2012; Moustafa et al, 2015; Weigard, Huang-Pollock, & Brown, 2016; Weigard & Huang-Pollock, 2014; Wiecki, Poland, & Frank, 2015) literatures.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, substantial heterogeneity in neurocognitive performance is also found in depression (McClintock, Husain, Greer, & Cullum, 2010), with evidence that executive dysfunction is not observed among depressed patients who demonstrate valid effort during testing (Benitez, Horner, & Bachman, 2011; Rohling, Green, Allen, & Iverson, 2002). However, even though motivation-cognition interactions on performance are relevant to a wide range of processes outside of WM (Botvinick & Braver, 2015; Braver et al, 2014) and are also observed among externalizing disorders (Luman, Oosterlaan, & Sergeant, 2005), the association between externalizing behavior and executive dyscontrol survives even when task engagement is controlled (Huang-Pollock et al, 2016; Huang-Pollock, Mikami, Pfiffner, & McBurnett, 2007; Shanahan, Pennington, & Willcutt, 2008; Shiels et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research has explored the concept that reciprocal paths, in which earlier social skills influence the subsequent development of EFs, may exist (Carlson, 2009; Lewis and Carpendale, 2009; Moriguchi, 2014; van Lier and Deater-Deckard, 2016). Indeed, it has long been theorized that humans develop higher mental functions within the context of interpersonal activity and social relationships (Luria, 1966; Vygotsky, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…This idea that EF development occurs via social interactions has been scientifically explored, primarily through the study of adult-child social interactions in scaffolding EFs (Landry et al, 2002; Bibok et al, 2009; Hughes and Ensor, 2009; Lewis and Carpendale, 2009; Blair et al, 2011; Roskam et al, 2014; de Wilde et al, 2016). However, a small but growing body of literature has assessed this in terms of peer interactions (Moriguchi, 2014; van Lier and Deater-Deckard, 2016). This body of literature has provided evidence that social interactions with peers are essential to developing self-regulation (Lindsey and Colwell, 2003) and EFs such as cognitive flexibility (Bateson, 2005) and inhibitory control (Peterson and Flanders, 2005).…”
Section: Introductionmentioning
confidence: 99%